Resolução CSMPF nº 128, de 8 de maio de 2012 - Roberto Monteiro Gurgel Santos; Deborah Macedo Duprat de Britto Pereira; Sandra Veronica Cureau; Maria Caetana Cintra Santos; Alcides Martins; Rodrigo Janot de Monteiro de Barros; Joao Francisco Sobrinho; Aurelio Virgilio Veigas Rios; Jose Flaubert Machado Araujo; Raquel Elias Ferreira Dodge (DOU, Brasília, DF, 13 jun. 2012. Seção 1, p. 90., 2012)
Dispõe sobre o Regimento Interno da 2ª Câmara de Coordenação e Revisão do Ministério Público Federal.